2019
DOI: 10.1017/wsc.2019.64
|View full text |Cite
|
Sign up to set email alerts
|

Band sowing with hoeing in organic grains: I. Comparisons with alternative weed management practices in spring barley

Abstract: Weeds remain the foremost production challenge for organic small grain farmers in the northeastern United States. Instead of crops sown in narrow, single-line rows, band sowing offers a more uniform spatial arrangement of the crop, maximizing interspecific while reducing intraspecific competition. Weeds in the inter-band zone are controlled by cultivating with aggressive sweeps; tine harrowing can target weeds in both intra- and inter-band zones. Field experiments in Maine and Vermont in 2016 and 2017 evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Maybe a system combining row widening (to increase intra-row weed suppressiveness of spinach plants) and a sequence of broadcast harrowing and inter-row hoeing (to maximise weed control efficacy) can outperform harrowed systems with narrow row spacing. In spring barley (Hordeum vulgare L.) at a density of 325 plants m −2 , McCollough et al [17] indeed found lower weed biomass per m 2 in systems with band seeding (12.7 cm bands spaced 15.2 cm apart) or 22.8-cm-wide single rows managed with harrowing and inter-row hoeing with 12.7 cm knives than in single-row systems with narrow (16.5 cm) row spacing managed with harrowing.…”
Section: Impact Of Plant Spacing Managementmentioning
confidence: 99%
“…Maybe a system combining row widening (to increase intra-row weed suppressiveness of spinach plants) and a sequence of broadcast harrowing and inter-row hoeing (to maximise weed control efficacy) can outperform harrowed systems with narrow row spacing. In spring barley (Hordeum vulgare L.) at a density of 325 plants m −2 , McCollough et al [17] indeed found lower weed biomass per m 2 in systems with band seeding (12.7 cm bands spaced 15.2 cm apart) or 22.8-cm-wide single rows managed with harrowing and inter-row hoeing with 12.7 cm knives than in single-row systems with narrow (16.5 cm) row spacing managed with harrowing.…”
Section: Impact Of Plant Spacing Managementmentioning
confidence: 99%
“…Widening row spacing while maintaining the seeding rate has opposing effects on intra‐row resource availability, simultaneously increasing light penetration into the crop canopy (Kolb et al, 2012) and intensifying competition (Regnier and Bakelana, 1995; Weiner et al, 2001). In wide‐row hoed cereal systems, Kolb et al (2010, 2012) and McCollough et al (2020) observed that weeds remaining in the intra‐row zone were larger, with increased individual biomass and height compared to narrow‐row and standard cropping strategies. Heightened intra‐specific competition is also associated with the wide‐row sowing; when seeding rate is maintained while row spacing is increased, crop density in the intra‐row becomes more crowded, resulting in greater competition between individual crop plants (Regnier and Bakelana, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The practice of widening row spacings to distances ranging from 15 to 30 cm to accommodate inter-row hoeing with aggressive shares constitutes a recent topic of research (Kolb et al, 2010(Kolb et al, , 2012McCollough et al, 2020;Melander et al, 2003Melander et al, , 2018. In the hoed system, cereals are cultivated much like a row crop; this practice has started to garner adoption as an improved weed management strategy among growers in Northern Europe.…”
mentioning
confidence: 99%
“…Because band sowing relies on crop-weed competition for the successful suppression of weeds in the intra-band zone, cereal crops are likely best suited for band sowing. However, in our related work in spring barley, band sowing with hoeing effects on weed density, biomass, and crop yield were inconsistent (McCollough et al 2020). It is important to note that our focus was on summer annual weeds.…”
mentioning
confidence: 89%